Hubungan Pemberian Remdesivir dengan Durasi Rawat Inap pada Pasien COVID-19 di Rumah Sakit Al-Islam Bandung - Achmad Firar Khairi; Heni Muflihah; Meta Maulida Damayanti (Bandung Conference Series: Medical Science, 2022)
Abstract. Coronavirus disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which is a new type of corona virus. One of repurposive therapy recommended for COVID-19 patients is remdesivir. Few studies have examined the use of remdesivir as an anti-viral drug in Indonesia. The benefits of clinical improvement can be indicated by the length of stay (LOS). This study aims to analyze the relationship between remdesivir administration and the LOS in COVID-19 patients at Al-Islam Hospital Bandung. This study is an observational analytic study using a retrospective cohort design and medical record data. The subjects of the study were confirmed COVID-19 patients who were hospitalized at Al-Islam Hospital Bandung for the period June-July 2021. The data taken included clinical characteristics, oxygen saturation (SpO2), remdesivir therapy, and LOS using purposive sampling technique. The total study subjects were 111 patients consisting of 55 people in the remdesivir group and 56 people in the combination remdesivir comparison group. There were 50 patients (89%) in the remdesivir group (89%) and 40 people (71%). The remdesivir group was mostly female as many as 33 people (60%). LOS for men had a median of 9 days, 3 days longer than for women. LOS in the remdesivir group had a median of 5 (interquartile range (IQR) 3-12) days, while the combination remdesivir had a median of 9 (IQR 4-16) days which was statistically significant (P-value <0.0001). It can be concluded that there is a relationship between the administration of remdesivir and LOS of COVID-19 patients. The combination of remdesivir with other antivirals needs to be evaluated for indications considering that it does not increase the benefit of improving LOS. Abstrak. Coronavirus disease 2019 (COVID-19) merupakan penyakit infeksi yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) yang merupakan virus korona jenis baru. Diantara terapi repurposive yang direkomendasikan pada pasien COVID-19 salah satunya remdesivir. Belum banyak penelitian yang mengkaji penggunaan remdesivir sebagai obat anti virus di Indonesia. Salah satu indikator manfaat perbaikan klinis dapat dilihat berdasarkan durasi rawat inap. Tujuan penelitian menganalisis hubungan pemberian remdesivir dengan durasi lama rawat inap pada pasien COVID-19 di RS Al-Islam Bandung. Penelitian ini merupakan analitik observasional menggunakan desain kohort retrospektif dan data rekam medik. Subyek penelitian adalah pasien terkonfirmasi COVID-19 yang menjalani rawat inap di Rumah Sakit Al-Islam Bandung periode Juni-Juli 2021. Data yang diambil meliputi karakteristik klinis, saturasi oksigen (SpO2), terapi remdesivir, dan durasi rawat inap menggunakan teknik purposive sampling. Total subyek penelitian berjumlah 111 pasien terdiri dari 55 orang kelompok remdesivir dan 56 orang kelompok pembanding remdesivir kombinasi. Pasien COVID-19 derajat tidak berat (SpO2 90%) pada kelompok remdesivir sebanyak 50 orang (89%) dan remdesivir kombinasi 40 orang (71%). Kelompok remdesivir sebagian besar berjenis kelamin wanita sebanyak 33 orang (60%). Durasi rawat inap pria memiliki median 9 hari, 3 hari lebih lama dari wanita. Durasi rawat inap kelompok remdesivir memiliki median 5 (interquartile range (IQR) 3-12) hari, sedangkan remdesivir kombinasi memiliki median 9 (IQR 4-16) hari yang secara statistik berbeda bermakna (P-Value <0.0001). Dapat disimpulkan terdapat hubungan antara pemberian remdesivir dan durasi rawat inap pasien COVID-19. Kombinasi remdesivir dengan antivirus lain perlu dievaluasi indikasinya mengingat tidak menambah manfaat perbaikan durasi rawat inap.